(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The degree of accuracy of experiments is important in studying the processes of synthesis of melamine formaldehyde resin. For this purpose, using the Maple computer program, the level of accuracy of the experiments was studied.